O direito fundamental à moradia digna - D'Ambrosio, Daniela (2013)
This dissertation presents the right to adequate housing as a fundamental right. Describes the content of that right, his prediction in the Federal Constitution, in legislation and in international human rights protection and exposes the gap between these predictions and reality. Comes from the huge number of people without adequate housing, comprising spaces characterized by the absence of the state. Identified are responsible for fulfilling that right and discussed their exposure to liability, as well as some possible ways of action of public authorities representatives of the three Powers. At the end, were brought into consideration three case studies that illustrate the points made in the theoretical and demonstrate the way in which they conducted some urban land conflicts